Client Intimacy & Performance Advice: Determinants of Trust in the Public Accountant - SME Client Relationship - Michael Cherry; Dianne McGrath; Chris Baumann (Australasian Accounting, Business and Finance Journal, 2018)
This multi-discipline research investigated the determinants of trust in the relationship between Australia’s public accountants and their small and medium-sized (SME) clients. In excess of four hundred SME owners, across Australia, were surveyed to test a proposed model and client intimacy variables were found to be the most significant predictors of trust in this important relationship. Offer-related variables, primarily the provision of advisory or performance-related services (rather than conformance-related services), were also found to be significant, however, at a lesser level than client intimacy and relationship variables. The multi-dimensionality of the trust construct was also highlighted.
Keywords: Trust; trust multi-dimensionality; public accountant; SME; conformance services; performance services; client intimacy; advisory services.